Satisfaction with Inclusive Education Services and its Relationship with Father and Mother Involvement: Satisfaction with Inclusive Education Services and its Relationship with Father and Mother Involvement - Annas Dwi Setyarini; Yunita Hardian Putri; Fatma Putri Sekaring Tyas; Alfiasari (Journal of Family Sciences, 2021)
Parental involvement in education is essential, especially for children with special needs and the existence of inclusive schools supports children's education fairly so that inclusive education services need to prioritize services to achieve parental satisfaction. The purpose of this study was to analyze parental satisfaction with inclusive education services and their relationship to parental involvement. This research was conducted in one of the inclusive schools in East Jakarta. Samples in this study are mothers and fathers from intact families with children with special needs who attend inclusive schools with purposive sampling technique with as many as 30 married couples. The results show a significant positive relationship between the variables of mother's satisfaction with father's satisfaction and father's engagement with father's satisfaction. Moreover, mother’s engagement was significantly related to mother’s education, while mother’s satisfaction positively correlated with mother’s age. A significant negative relationship was found between mother's satisfaction and father's education; father's engagement with child's age and length of getting inclusive services. The effect test found that the father's satisfaction was significantly affected by father's involvement and mother's satisfaction, while mother’s satisfaction was significantly affected by mother’s age and father's satisfaction. Inclusive schools need to provide optimal services and involve parents in schools to feel satisfied.